The treatment approach of patients and their families and impact on SMS reminder toward OPD follow up of psychotic patients. - Mehmood, Nasir; Talib, Uroosa; Raza ur Rehman; Naeem, Farooq (International Journal of Endorsing Health Science Research, 2021)
Background: The patient's follow-up is a significant challenge for managing psychiatric illness, especially psychotic disorders. Although many factors affect patients' clinical non-attendance with psychosis, the approach of patients and their families toward medication influences treatment follow up. The study evaluates the patient's and family's approach regarding OPD follow up and the effect of SMS reminder on OPD follow up of patients with psychosis. Methodology: This study was conducted on a psychotic patient attending OPD at Karwan e Hayat, Karachi. A total of 248 patients were randomly divided into two groups, the SMS reminder group and the treatment-as-usual or control group. Computer-based SMS to improve patient's follow-up was sent in Urdu and English to the SMS group. A total of four reminder messages were sent to the SMS group within 15 days of each clinical appointment over a period of 24-weeks, while no message was sent to the control group. Results: All patients (Intervention & Control groups) were divided further into two groups based on the caring family approach reflected through several follow-ups, including a poor follow up group with less than five visits and an appropriate follow-up group having five or more than five visits. The impact of SMS follow-up reminders on both groups was observed through OPD follow-ups. At baseline, all groups were comparable, but after a 3-month appropriate group of intervention were found with a significant (p=0.053) increase in the number of follow-ups compared to patients with poor follow-up groups. Conclusion: It is concluded from the study results that the SMS reminders are an effective intervention in those psychotic patients and families who have a positive approach to illness.